Congruence of higher education: determinants and effects of the allocation process in the labor market, applied case to Colombia (2016)
This paper provides new evidences to the literature of assignment in the labor market for the Colombian case. Specifically it focuses on the existing relationship between acquired human capital in higher education and its congruence in the labor market. Differing from previews studies, the misallocation analysis is not only based on the horizontal component and the educational mismatch, but it also includes the vertical mechanism (vertical mechanism is related to skills mismatch and horizontal mechanism is related to professional career mismatch). Another contribution is how we measure the abilities through an exploratory factor analysis. The data are taken from the Survey of Graduates of Higher Education Institutions 2014, provided by OLE. We employ a two-step treatment effect method proposed by Heckman (1974, 1979) and Lee (1978)), we found that generic abilities raise the probability of horizontal mismatch and diminish the probability of vertical mismatch. On the other hand, specific abilities lower the probability of both horizontal and vertical mismatch. In terms of wages, we found evidence that confirmed the results of the assignment models because it exists a wage penalty for the mismatched individuals (Sattinger, 1993).